2014
DOI: 10.1124/jpet.114.216135
|View full text |Cite
|
Sign up to set email alerts
|

Different Contributions of Dopamine D1 and D2 Receptor Activity to Alcohol Potentiation of Brain Stimulation Reward in C57BL/6J and DBA/2J Mice

Abstract: C57BL/6J (C57) and DBA/2J (DBA) mice respond differently to drugs that affect dopamine systems, including alcohol. The current study compared effects of D1 and D2 receptor agonists and antagonists, and the interaction between D1/D2 antagonists and alcohol, on intracranial self-stimulation in male C57 and DBA mice to determine the role of dopamine receptors in the effects of alcohol on brain stimulation reward (BSR). In the initial strain comparison, dose effects on BSR thresholds and maximum operant response r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Given that genetic background strongly influences mouse LORR (Boyce-Rustay et al, 2008; Crabbe, 2012; Crabbe, Metten, Cameron, & Wahlsten, 2005) and the mice tested by Tanchuck-Nipper and colleagues were on a C57BL/6J × 129/SvJ background (as opposed to the pure C57BL/6J background used here), a plausible explanation for this discrepancy is that sex differences in the LORR are background-dependent. This would be another interesting question to explore in follow-up work, perhaps similar to what other studies have shown reporting the influence of genetic background on response to ethanol in mice (Fish, DiBerto, Krouse, Robinson, & Malanga, 2014). Aside from this question, we found that LORR durations were significantly shortened by CIE in both males and females – consistent with the development of tolerance to this measure of intoxication (as previously reported in rats and male C57BL/6J mice [Daut et al, 2015; Walls, Macklin, & Devaud, 2012]).…”
Section: Discussionmentioning
confidence: 62%
“…Given that genetic background strongly influences mouse LORR (Boyce-Rustay et al, 2008; Crabbe, 2012; Crabbe, Metten, Cameron, & Wahlsten, 2005) and the mice tested by Tanchuck-Nipper and colleagues were on a C57BL/6J × 129/SvJ background (as opposed to the pure C57BL/6J background used here), a plausible explanation for this discrepancy is that sex differences in the LORR are background-dependent. This would be another interesting question to explore in follow-up work, perhaps similar to what other studies have shown reporting the influence of genetic background on response to ethanol in mice (Fish, DiBerto, Krouse, Robinson, & Malanga, 2014). Aside from this question, we found that LORR durations were significantly shortened by CIE in both males and females – consistent with the development of tolerance to this measure of intoxication (as previously reported in rats and male C57BL/6J mice [Daut et al, 2015; Walls, Macklin, & Devaud, 2012]).…”
Section: Discussionmentioning
confidence: 62%
“…An additional plausible explanation is suggested by the current study and involves the lower D1 receptor levels in Drd2 +/− and Drd2 −/− C mice. D1 receptor antagonism prevents the reward potentiating effects of alcohol in the intracranial self-stimulation paradigm (Fish et al, 2014 ) and decreases ETOH seeking as well as ETOH conditioned place preference (Liu and Weiss, 2002 ; Hamlin et al, 2007 ; Chaudhri et al, 2009 ; Bahi and Dreyer, 2012 ; Pina and Cunningham, 2014 ; Sciascia et al, 2014 ; Young et al, 2014 ), while D1 agonism increases ETOH self-administration (D−souza et al, 2003 ) and ethanol-induced motor sensitization (Abrahao et al, 2011 ). Since the rewarding properties of ETOH are decreased by D1 receptor antagonism, we conclude that the lower D1 striatal receptor levels in Drd2 +/− and Drd2 −/− C mice contribute to their lower ETOH intake/preference, compared with Drd2 +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…LY341495 (0.1–0.3mg/kg) was used at a dose that improved depression-like behavior in the chronic corticosterone-treated mice ( Ago et al, 2013b ). SCH39166 (0.1–0.2mg/kg) and raclopride (0.03–0.1mg/kg) were used at doses that affected reward-related behaviors in mice ( Fish et al, 2014 ; Price and Middaugh, 2004 ).…”
Section: Methodsmentioning
confidence: 99%